Evaluation of Cognition Enhancing Activities of Telmisartan, Nimodipine and their Combination in REM Sleep Deprived Wistar Rats - Siddalingappa, Mohan Kumar; Vittalrao, Amberkar Mohanbabu; Kamalkishore, Meena Kumari; Mamulpet, Vinay (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: Sleep Deprivation (SD) may lead to the failure of advanced neural functions, including decision-making, learning and memory. Studies show that nimodipine plays a role in intracellular Ca^2+ to reduced influx of Ca^2+ into mitochondria. Thereby, nimodipine improves the spatial cognition and elevates hippocampal acetylcholine. Telmisartan, has been proven to improve cognitive function in scopolamine induced amnesic rats. Aims: To evaluate the cognition enhancing activities of telmisartan and nimodipine in REM sleep deprived Wistar rats. Materials and Methods: SD rats were treated with telmisartan (3.6mg/kg), nimodipine (5mg/kg) and combination of both for 4 weeks. Morris water maze was done to estimate the spatial learning and memory. Brain glutathione, malondialdehyde, acetylcholinesterase, Brain Derived Neurotropic Factor (BDNF) and histopathological examinations were done. Results were analysed by ANOVA followed by post hoc Tukey’s test. Brain samples were sectioned for histopathological examination. Results: Increase in oxidative stress following REM sleep deprivation was reversed in chronic study. Chronic intake of telmisartan, nimodipine and combination of both the drugs mitigated spatial learning and memory deficit in Wistar rats induced by REM sleep deprivation. In telmisartan treated group there was significant increase in BDNF levels (p<0.05) as compared to SD rats. The histopathological sections showed less damaged neurons in telmisartan, nimodipine and their combination group. Conclusion: Current study demonstrated that telmisartan, nimodipine and combination of these two drugs reversed the sleep deprivation induced cognitive impairment by reducing oxidative stress, enhancing cholinergic activity, BDNF levels and histopathological findings support the above fact. However, further studies are essential to confirm the result.
Keywords: Cognition; Nimodipine; Telmisartan; Sleep deprivation; BDNF